2019
DOI: 10.3892/etm.2019.8322
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis: A permanent new challenge for dermatologists (Review)

Abstract: Considering that most of the patients (>2/3) are diagnosed with psoriasis in the cutaneous form long before the joint damage occurs and, in these conditions, a significant proportion of them is found in the dermatologist's initial records, a question must be asked: when is it necessary to send these patients to a rheumatology consultation? The recognition of psoriatic arthritis in patients with vulgar psoriasis and the dermatologist's ability to differentiate it from other arthritis, offers the opportunity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, it is estimated that PsA in approximately 10–15% of patients with psoriasis remains undiagnosed or misdiagnosed 19 . Hence, it is vital to routinely screen patients with psoriasis for the diagnosis of PsA in a dermatology clinic 20 . Delay of PsA diagnosis can lead to irreversible joint damage, even if a significant improvement in psoriasis occurs 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is estimated that PsA in approximately 10–15% of patients with psoriasis remains undiagnosed or misdiagnosed 19 . Hence, it is vital to routinely screen patients with psoriasis for the diagnosis of PsA in a dermatology clinic 20 . Delay of PsA diagnosis can lead to irreversible joint damage, even if a significant improvement in psoriasis occurs 5 .…”
Section: Discussionmentioning
confidence: 99%
“… 19 Hence, it is vital to routinely screen patients with psoriasis for the diagnosis of PsA in a dermatology clinic. 20 Delay of PsA diagnosis can lead to irreversible joint damage, even if a significant improvement in psoriasis occurs. 5 Therefore, dermatologists have a pivotal role in early identification of patients with PsA and prevention of irreversible joint damage.…”
Section: Discussionmentioning
confidence: 99%
“…This is a bilateral condition and the symptoms include red, painful eyes with pericorneal congestion, reduction or even loss of visual acuity and photophobia may also occur (1,6,12,19). Previous studies have demonstrated the association between uveitis and different types of psoriasis, but uveitis is more frequent among patients with HLA B27-positive psoriatic arthritis (20); however, the association is not fully understood. Uveitis may also develop in patients with pustular psoriasis (5,12).…”
Section: Ophthalmological Changesmentioning
confidence: 99%
“…A total of 20-30% of patients with psoriasis also develop psoriatic arthritis, which over time leads to severe, deforming joint injuries, which often cause disability [5]. In the absence of a set of specific criteria for the diagnosis of psoriatic arthritis, the most commonly used method for recognizing and monitoring this condition remains the clinical aspect [6].…”
Section: Introductionmentioning
confidence: 99%